The Imperial City of Cologne : From Roman Colony to Medieval Metropolis (19 B.C.-1125 A.D.) - Huffman, Joseph P., 1959- (Book collections on Project MUSE., 2018)
The Imperial City of Cologne: From Roman Colony to Medieval Metropolis (19 B.C.-1125 A.D.) is an urban history of Cologne from its imperial Roman origins as a northeastern frontier military outpost to a medieval metropolis on the German Empire's northwestern border. This first history of Cologne, available in English, challenges received notions of late Roman ethnic identities, a Dark Age collapse of urban life, devastating Viking and Magyar incursions, and the origins of medieval urban government.